The Poison of Cyberbullying in Destroying Children's Sense of Empathy - Shinta Shinta; Akif Khilmiyah (Universitas Pendidikan Ganesha, 2024)
Cyberbullying is usually carried out because of the perpetrator's low level of empathy and has the potential to erode the victim's sense of empathy, making it possible for the victim to cyberbullying other people as well. This research aims to bibliometrically analyze articles about the relationship between cyberbullying and empathetic attitudes from 2010 to 2024. Analysis was conducted using VOSviewers to obtain network map visualization, Scopus AI to identify references most relevant to the research topic, and reviewing all contents of selected journals to conduct a comprehensive analysis. The research results show that analysis via Vosviewer produced 16 clusters and Scopus AI produced 8 points regarding the relationship between cyberbullying and empathy, which can be summarized that cyberbullying can result in mental health disorders, both the erosion of good behavior, especially empathy in the perpetrator and the victim can experience depression, even leading to suicide or loss of empathy within yourself because you want revenge for carrying out cyberbullying against other people. Cyberbullying behavior that can endanger a child's sense of empathy can be reduced by providing digital literacy assistance, strengthening character education, and getting used to always being empathetic, both offline and online, towards other people.